2021
DOI: 10.1111/ijcs.12656
|View full text |Cite
|
Sign up to set email alerts
|

Being like others vs. being different: Wearable technology and daily practices of 50+ consumers in Russia and Finland

Abstract: This is a qualitative study of consumers aged 50+ and their daily practices connected to wearable devices (smartwatches and fitness trackers). Drawing on the practice theory, we seek to uncover how participation in such practices might enhance users’ well‐being as an integral part of social sustainability. We assume that both ageing and well‐being are not pre‐given but they rather co‐evolve when users of wearables engage in situated practices. Hence, wearables such as smartwatches and fitness trackers might po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 105 publications
0
33
0
Order By: Relevance
“…Researchers have also shown that wearable technologies can have a positive effect on consumers' well-being, thus suggesting an effect on buying intention (Morozova & Gurova, 2021). However, the current study is the first to compare how media richness in AR devices can affect engagement and buying intention through the mediating roles of emotion (arousal and pleasure) and cognitive responses (attitudes and information quality).…”
Section: Theoretical Contributions and Implicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…Researchers have also shown that wearable technologies can have a positive effect on consumers' well-being, thus suggesting an effect on buying intention (Morozova & Gurova, 2021). However, the current study is the first to compare how media richness in AR devices can affect engagement and buying intention through the mediating roles of emotion (arousal and pleasure) and cognitive responses (attitudes and information quality).…”
Section: Theoretical Contributions and Implicationsmentioning
confidence: 85%
“…Despite the growing number of studies in AR and VR, most studies have been focused on a restricted number of theories such as technology adoption, which are unable to study the effectiveness of promotional messages in consumer attitudes (Shahab et al., 2021). Researchers have also shown that wearable technologies can have a positive effect on consumers’ well‐being, thus suggesting an effect on buying intention (Morozova & Gurova, 2021). However, the current study is the first to compare how media richness in AR devices can affect engagement and buying intention through the mediating roles of emotion (arousal and pleasure) and cognitive responses (attitudes and information quality).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the Internet of Things (IoT) can dramatically change consumers' lives and ultimately improve individuals' well‐being (Morozova & Gurova, 2021). As such, the IoT is revolutionizing the way healthcare services are delivered, especially for individuals suffering from chronic illnesses (Menvielle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the widespread use of mobile technology, today’s consumer uses mobile apps (Al‐Adwan & Sammour, 2021) and wearable devices (Morozova & Gurova, 2021), buys goods online, relies on peer opinions on social media (SM) (Ma et al., 2021), and has several other specific characteristics. Retailers need to follow the habits of customers and adapt their presence accordingly (Hult et al., 2019).…”
Section: Introductionmentioning
confidence: 99%